Analisis Nilai Lahan Kecamatan Gondomanan Kota Yogyakarta Menggunakan Aplikasi SIG dan Penginderaan Jauh - Nurma Sari, Anisa, Agus Anggoro Sigit, S. Si, M. Sc (2016)
Land is natural resources which is very important for human life. The need of land increase in every year considering the unchanged of land size and it caused level of land demand andget influential in rising degree of land value. Land condition with high potentially will have highvaluebut land with less potentially will have low value. This research use survey method with Stratified Purposive Sampling techniqueand I did the analysis with quantitative overlay method to process the land value distribution, and after that I did the survey to check the land suitability with the land price.Parameter that used in this researchare land use , accessibility positive , accessibility negative, and completeness utility. The result shows that Gondomanan Subdistrict has 3 class of land value high, medium, and low. The village which has highest land value is Ngupasan with size of land 18,53Ha (30,78% ) and the village which has lowest is Prawirodirjan with size of land 9,47Ha(22,74%). Land use factors the most influential factor in the high value of land in the Gondomanan Subdistrict is land use in the form of trade and services and settlement. Keywords: Land Value, Geographical Information System and Remote Sensing